Lightweight Micro-Expression Recognition on Composite Database - Nur Aishah Ab Razak; Shahnorbanun Sahran (Applied Sciences, 2023)
The potential of leveraging micro-expression in various areas such as security, health care and education has intensified interests in this area. Unlike facial expression, micro-expression is subtle and occurs rapidly, making it imperceptible. Micro-expression recognition (MER) on composite dataset following Micro-Expression Grand Challenge 2019 protocol is an ongoing research area with challenges stemming from demographic variety of the samples as well as small and imbalanced dataset. However, most micro-expression recognition (MER) approaches today are complex and require computationally expensive pre-processing but result in average performance. This work will demonstrate how transfer learning from a larger and varied macro-expression database (FER 2013) in a lightweight deep learning network before fine-tuning on the composite dataset can achieve high MER performance using only static images as input. The imbalanced dataset problem is redefined as an algorithm tuning problem instead of data engineering and generation problem to lighten the pre-processing steps. The proposed MER model is developed from truncated EfficientNet-B0 model consisting of 15 layers with only 867k parameters. A simple algorithm tuning that manipulates the loss function to place more importance on minority classes is suggested to deal with the imbalanced dataset. Experimental results using Leave-One-Subject-Out cross-validation on the composite dataset show substantial performance increase compared to the state-of-the-art models.